COLLECTIVE TRAUMA IN THE NARRATIVE OF THE 1999 SAMBAS INCIDENT: Trauma Kolektif Dalam Narasi Peristiwa Sambas 1999 - Nur Shoimah; Ba'in (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The 1999 Sambas Incident was an ethnic conflict involving two ethnic groups, the Sambas Malay and the Madurese, in West Kalimantan. This incident resulted in mass violence and large-scale displacement, particularly among the Madurese. The impact of this conflict was not only physical and financial, but also gave rise to collective trauma that then influenced inter-ethnic social relations until the post-conflict period. This article aims to analyze the background and process of the 1999 Sambas Incident, and to understand how the event was then constructed and inherited as a collective trauma within the community groups involved. This study uses historical research methods consisting of heuristics, source criticism, interpretation, and historiography. Research sources were obtained through archives, government reports, mass media coverage, and relevant previous scientific works. This research analysis uses the concept of collective trauma by Jeffrey C. Alexander and Gilad Hirschberger, as well as the concept of violence by Johan Galtung. The results of the study indicate that the collective trauma of the 1999 Sambas Incident was passed down from generation to generation, through family and community narratives. The inherited collective trauma then becomes a group identity and ultimately influences post-conflict interethnic relations. Thus, the collective trauma of this event serves not only as a memory of the past but also as a social lens for interpreting relationships with other groups and shaping boundaries within society.